2020
DOI: 10.1158/1541-7786.mcr-19-0726
|View full text |Cite
|
Sign up to set email alerts
|

Cdc42 Mediates Cancer Cell Chemotaxis in Perineural Invasion

Abstract: Perineural invasion (PNI) is an ominous form of cancer progression along nerves associated with poor clinical outcome. Glial derived neurotrophic factor (GDNF) interacts with cancer cell RET receptors to enable PNI, but downstream events remain undefined. We demonstrate that GDNF leads to early activation of the GTPase Cdc42 in pancreatic cancer cells, but only delayed activation of RhoA and does not affect Rac1. Depletion of Cdc42 impairs pancreatic cancer cell chemotaxis toward GDNF and nerves. An siRNA libr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Since Rac, RhoA, and Cdc42 are key molecules of cell motility 13 15 , we confirmed their protein expression levels in each group (Fig. 4 A).…”
Section: Resultsmentioning
confidence: 58%
“…Since Rac, RhoA, and Cdc42 are key molecules of cell motility 13 15 , we confirmed their protein expression levels in each group (Fig. 4 A).…”
Section: Resultsmentioning
confidence: 58%
“…As such, the GEF(s) linking CD99 to CDC42 activity remains to be identified. Interestingly, a β-Pix-CDC42 pathway has recently been identified to regulate perineural invasion in pancreatic cancer ( Chernichenko et al, 2020 ). The basis of the small increases in total CDC42 detected upon CD99 depletion are unclear, but might result from the altered activity of transcription factors and/or post-translational modifications of CDC42 that occur downstream of CDC42 activation and actin reorganisation ( Corry et al, 2020 ; Haga and Ridley, 2016 ; Hall, 2012 ; Medjkane et al, 2009 ; Perona et al, 1997 ).…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that CDC42 was a target gene of porcine miR-185. As a chemokine that mediates tumors, CDC42 can participate in the migration and invasion of various cancer cells [33]. Previous research reported that microRNA-384 inhibits proliferation, migration and invasion of glioma by targeting at CDC42 [34].…”
Section: Discussionmentioning
confidence: 99%